Neighborhood Environments and Utilitarian Walking Among Older vs. Younger Rural Adults - Lee, Chanam; Lee, Chunkeun; Stewart, Orion T.; Carlos, Heather A.; Adachi-Mejia, Anna; Berke, Ethan M.; Doescher, Mark P. (Frontiers in Public Health, 2021)
Introduction: Walking has the potential to promote health across the lifespan, but age-specific features of neighborhood environment (NE) linked with walking have not been adequately characterized. This study examines the relationships between NE and utilitarian walking among older versus younger adults living in US rural towns. Methods: Data for this cross-sectional study came from telephone interviews in 2011-12 with 2,140 randomly sampled younger (18-64 years, n=1,398) and older (65+ years, n=742) adults, collecting personal and NE perception variables. NE around each participant’s home was also measured objectively using Geographic Information System techniques. Separate mixed-effect logistic regression models were estimated for the two age groups, predicting the odds of walking at least once a week. Results: Perceived presence of crosswalks and pedestrian signals was significantly related to utilitarian walking in both age groups. Among older adults, unattended dogs, lighting at night, and religious institutions were positively, while steep slope was negatively associated with their walking. For younger adults, traffic speed (negative, -), public transportation (positive, +), malls (-), cultural/recreational destinations (+), schools (+), and resource production land uses such as farms and mines (-) were significant correlates of walking. Conclusion: Different characteristics of NE are associated with utilitarian walking among younger versus older adults in US rural towns. Optimal modifications of NE to promote walking may need to reflect these age differences.